2021
DOI: 10.1007/s10608-021-10265-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Experiential Avoidance in terms of COVID-19 Fear and Pandemic Emotional Distress Symptoms Among Latinx Adults

Abstract: Background The outbreak of the novel 2019 SARS2-Coronavirus disease (COVID-19) has led to substantial psychological distress across the United States and the world. However, emerging work suggests that prominent COVID-19 consequences such as fear of COVID-19 infection and emotional distress resulting from economic adversity and social distancing may afflict the Latinx population disproportionately. The current study sought to investigate the influence of experiential avoidance (EA), or an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…We found the participants showed an increased risk of IA. Previous studies demonstrated that the fear of COVID‐19 was related to experiential avoidance (Mayorga et al, 2021), and might further cause greater psychological distress among college students, including substance use, emotional suppression (Levin et al, 2012). Therefore, more attention should be paid to IA among undergraduates, especially for those who experience more serious traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…We found the participants showed an increased risk of IA. Previous studies demonstrated that the fear of COVID‐19 was related to experiential avoidance (Mayorga et al, 2021), and might further cause greater psychological distress among college students, including substance use, emotional suppression (Levin et al, 2012). Therefore, more attention should be paid to IA among undergraduates, especially for those who experience more serious traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a profound and robust impact on individuals’ mental health across populations ( Huang & Tsai, 2022 ; Stamatis et al, 2022 ; Thompson et al, 2022 ; Williams et al, 2022 ) and has particularly negatively affected individuals’ experiences with fear and anxiety of the COVID-19 pandemic ( Ahmed et al, 2021 ; Gritsenko et al, 2021 ; Mayorga et al, 2022 ; Warren et al, 2021 ). In response, researchers created and validated the Fear of COVID-19 Scale (FCV-19S) to measure individuals' fear of COVID-19 (FCV-19S; Ahorsu et al, 2022 ).…”
mentioning
confidence: 99%